(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Decision-makers tend to highlight the importance of their companies becoming resilient. The goal nevertheless stays hollow if there is no way to quantify and visualize firm resilience. However current scientific works appear to lack the drive for a robust foundation and empirical evidence, despite the emergence of resilience as a prominent topic in business and management literature. Hence this research is motivated by the specific objective of advancing the theory of firm resilience, addressing the imperative need for measures that capture its dynamic nature by encompassing both absorptive and adaptive firm capabilities. The research presents a grounded view of firm resilience and culminates in a six-part axiomatization, outlining which properties a conclusive resilience measure should possess. Considering the interdisciplinary nature of resilience research, suggestions from engineering disciplines are classified and presented. Their compatibility with the axiomatization is assessed, revealing a clear trend towards quantitative resilience measures. Additionally, a match that inherits all properties is identified. A call for further empirical research on the validity of the metric is emphasized, urging the exploration of other metrics alongside, given that this paper offers substantial guidance for future adjustments to measures of firm resilience.